ON THE CONTRIBUTION OF BASIC AND ULTRABASIC ROCKS IN THE ACCUMULATION OF THE PRODUCTS OF VOLCANIC AND HYDROTHERMAL ACTIVITY IN THE BALYGYCHAN-SUGOI TROUGH (NE RUSSIA) - Filimonova L.G.; Chugaev A.V. (My University, 2002)
The data available on the crustal structure of the Balygychan-Sugoi Trough and the mineralogy and geochemistry of the Mesozoic and Cenozoic gabbro, acid volcanics, and post-magmatic minerals of the Dukat Au-Ag ore field, Sn-Ag occurrences, and zones of dispersed multimetal mineralization are used to show the great role of basic magma material in the shaping of their chemical composition. The data reported here for the Sr isotopic compositions of the contrasting volcanic rocks and the post-magmatic minerals of the ore-bearing areas and for the mineral compositions of mafic and ultramafic inclusions in the acid volcanics suggest a connection between the successive periods of endogenic activity in the region and mantle convection and the belonging of the resulting products to a mantle-plume rock association.
Keywords: BASIC AND ULTRABASIC ROCKS; VOLCANIC AND HYDROTHERMAL ACTIVITY; BALYGYCHAN--SUGOI TROUGH; Cenozoic; Mesozoic; Cenozoic; Mesozoic; Мезозой; Кайнозой